The genus Promalactis Meyrick (Lepidoptera: Oecophoridae) in Cambodia, with description of eight new species - Jia, Yanyan; Wang, Shuxia; Bae, Yang-Seop (Zootaxa, 2018)
Nine species of the genus Promalactis Meyrick, 1908 are recorded from Cambodia. Eight species are described as new: P. latiuscula Wang, sp. nov., P. curvicornuta Wang, sp. nov., P. ostacantha Wang, sp. nov., P. apicuncata Wang, sp. nov., P. granulosa Wang, sp. nov., P. argentifasciaria Wang, sp. nov., P. quadrilobata Wang, sp. nov. and P. trifasciata Wang, sp. nov. One species is newly recorded for Cambodia: P. carinata Du, Li et Wang, 2011. Photographs of adults and genitalia are provided.